2011
DOI: 10.1111/j.1365-2605.2011.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

TCam‐2 seminoma cell line exhibits characteristic foetal germ cell responses to TGF‐beta ligands and retinoic acid

Abstract: Germ cell testicular cancer is understood to arise during embryogenesis, based on the persistence of embryonic germ cell markers in carcinoma in situ and seminoma. In this study, we examine the potential of the seminoma-derived TCam-2 cell line to be used as representative in functional analyses of seminoma. We demonstrate expression of several early germ cell markers, including BLIMP1, OCT3/4, AP2γ, NANOG and KIT. Many TGF-beta superfamily receptors and downstream transcription factors are also present in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 50 publications
(127 reference statements)
3
43
1
Order By: Relevance
“…This suggests KIT dependence of SE and possibly a KITLG saturated micro-environment (threshold level for effect on viability already suggested for KIT in [354]). In the SE cell line TCam-2 [359][360][361][362] Goddard and coworkers identified a small but significant decrease in viability upon KIT knock down [354]. In a similar experiment from our group we could not replicate this result, nor did we detect a consistent effect of KITLG knock down or exogeneous KITL addition on TCam-2 viability (results in supplementary data).…”
Section: Kit/kitlg In Germ Cell Cancercontrasting
confidence: 64%
“…This suggests KIT dependence of SE and possibly a KITLG saturated micro-environment (threshold level for effect on viability already suggested for KIT in [354]). In the SE cell line TCam-2 [359][360][361][362] Goddard and coworkers identified a small but significant decrease in viability upon KIT knock down [354]. In a similar experiment from our group we could not replicate this result, nor did we detect a consistent effect of KITLG knock down or exogeneous KITL addition on TCam-2 viability (results in supplementary data).…”
Section: Kit/kitlg In Germ Cell Cancercontrasting
confidence: 64%
“…Our previous results with juvenile mouse testes (Mithraprabhu et al , 2010) showed that activin exposure reduces KIT mRNA and protein levels, so we hypothesised that the highly conserved nature of gametogenesis would lead to a similar outcome in adult human testes where it is known that activin receptors are present in spermatogonia and Sertoli cells as well as in TGCT cells (Dias et al , 2008). We have also demonstrated functional activin receptors in the TCam-2 seminoma cell line, with activin A exposure resulting in higher expression of KIT and lower levels of the CIS and seminoma cell marker, AP2 γ (Hoei-Hansen et al , 2004; Young et al , 2011). …”
mentioning
confidence: 67%
“…Activin A treatment (50 ng ml −1 ; R&D Systems, Minneapolis, MN, USA) and follistatin (100 ng ml −1 ; R&D Systems) were added to media with 0.1% BSA for 48 h and samples were collected into PFA fixative (4%), RNAlater for RNA purification or set-up in the survival assay (all as described above). The selected treatments and concentrations were based on results from previous experiments with activin A and follistatin in mouse seminiferous tubule cultures and the human seminoma cell line, TCam-2 (Mithraprabhu et al , 2010; Young et al , 2011). …”
Section: Methodsmentioning
confidence: 99%
“…TCam-2 cells express markers of undifferentiated human fetal germ cells (21,24) and thus may be considered comparable to the germ cells within the earlier gestational ovaries utilized in this study (8 -12 weeks)). Using this stably transfected germ cell line, we demonstrated that PROK1, acting through PROKR1, is able to up-regulate phosphorylation of ERK.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of the PROK ligands and their receptors was characterized during key stages of ovarian development leading up to primordial follicle formation, and functional studies on the role of PROK signaling in regulating gene expression undertaken using a human germ cell tumor line, TCam-2 cells (17), stably transfected with the PROKR1 receptor. TCam-2 cells have been previously characterized as a model of human fetal germ cells, as they express numerous markers characteristic of germ cells during that period of development (21,24).…”
mentioning
confidence: 99%